Good Practices and Lecturer Perceptions of Open and Distance Learning Media Through UT Radio in Universitas Terbuka - Dhini, Bachriah Fatwa; Jamaludin; Kristina Anugerah Aji; Kusnindyah Puspito Hapsari; Hafid, Al; Nova Ade Yunita Abidin (LPPM Universitas Terbuka, 2024)
UT Radio, an internet-based radio broadcast service, serves as a multifaceted educational platform, offering general educational content, course tutorials, information dissemination about UT, and engaging educational entertainment. This study investigates the evolving landscape of UT Radio, which now includes live streaming on the UTTV YouTube channel and aligns with the podcasting trend. Podcasts, with their captivating packaging and focused episode content, have gained popularity as a medium for information dissemination. The research employs qualitative methods to identify effective practices and elucidate the experiences of lecturers using UT-Radio for teaching and learning. Subjects include lecturers, course materials, and UT-Radio teamwork. Data collection involves observation sheets, interviews, and documentation, with 248 lecturers participating. The questionnaire evaluates broadcaster performance and UT-Radio management, demonstrating high validity and reliability (rα broadcaster performance = .96, rα management of UT Radio = .94, Cronbach's Alpha = 0.79). Interviews with five informants reveal positive perceptions among lecturers, highlighting UT Radio's role in facilitating the learning process. While obstacles exist, such as limited tutor ability to create instructional media and varying usage of multimedia tools, positive enforcement and management practices are evident. Challenges, including internet constraints during remote broadcasts, are acknowledged, and suggestions for more interactive communication with students are emphasized. In conclusion, this study provides valuable insights into the dynamics of UT Radio as an educational tool, emphasizing the need for innovative learning media development to enhance the overall educational experience.